The Effect of Product Quality and Service Quality on Purchase Decisions that Impact on Consumer Satisfaction at Deolin.Co-Chocolate & Cookies In Bandung City - Dadang Munandar (Universitas Negeri Makassar, 2020)
This study aims to determine the effect of product quality and service quality on purchasing decisions that have an impact on consumer satisfaction at Deolin.co-Chocolate & Cookies in Bandung. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that product quality has a significant effect on purchasing decisions by 34.9%, hypothesis testing obtained a significance of 0.000 <0.05. Service quality has a significant effect on purchasing decisions by 45.0%, hypothesis testing obtained a significance of 0.000 <0.05. Product quality and service quality simultaneously have a significant effect on purchasing decisions by 51.2%, hypothesis testing obtained a significance of 0.000 <0.05. Purchasing decisions have a significant effect on consumer satisfaction by 31.3%, hypothesis testing obtained a significance of 0.000 <0.05.